Kharkiv Innovation System: Status, Challenges, and Prospects - Bubenko, P.T.; Gagauz, I.B.; Gusev, V.A.; Lukyanets, S.P. (Science and Innovation, 2024)
The implementation of the Regional Innovation System (RIS) Project in Kharkiv has been discussed. The history of the RIS Project, its structure, composition of innovation system elements, and status of their development have been described. The factors influencing the effectiveness of developed innovation system have been identified and discussed.